EP358/#948 Evaluating the racial/ethnic representation of targeted therapy clinical trials in gynecologic oncology: who is being left behind?. (4th December 2022) - Cotangco, Katherine; Johnson, Caitlin; Mann, Amandeep; Aliabadi, Arya; Liao, Cheng-I; Salani, Ritu; Cohen, Joshua; Kapp, Daniel; Chan, John K
Abstract : Objectives: It is unclear if targeted therapy trials represent the diversity of gynecologic oncology patients. Our objective was to evaluate racial representation of targeted therapy clinical trials in gynecologic oncology. Methods: From 2005–2021, all phase 3 clinical trials on bevacizumab, olaparib, niraparib, rucaparib, veliparib, atezolizumab, pembrolizumab, avelumab, cemiplimab, mirvetuximab, lenvatinib, and MEK inhibitors were identified from clinicaltrials.gov. Using the United States Cancer Registry (USCS) as comparison, Chi square analysis was performed. Results: Of 30 trials (n= 23, 155 patients), 24 were international and 6 were US trials. 26 trials were ovarian followed by 2 endometrial and 2 cervical cancer trials. The overall proportion of White patients was 79%, Asian 12%, Hispanic 3%, and Black women 3%. Compared to USCS, Black women were underrepresented in uterine (4% vs 10%), ovarian (5% vs. 15%), and cervical cancers (7% vs. 15%), p-value <0.05. The proportion of Hispanic women were underrepresented in uterine (0% vs. 8%), ovarian (3% vs. 9%), and cervical cancers (12% vs 16%), p-value <0.05. In the subset of US trials, Black (5% vs 9%) and Hispanic women (4% vs 9%) were underrepresented in ovarian and cervical cancer compared to USCS incidence data. The proportion of Black and Hispanic women enrolled in gynecologic cancer trials has not improved over this time period (3% Black and 3% Hispanic women). Conclusions: Black and Hispanic women were underrepresented in gynecologic cancers trials involving targeted therapies. Careful interpretation of these results and their real-world application in US women is necessary given their distinct host and tumor biology.